Identifikasi Penggunaan Dana Desa untuk Penanggulangan Kemiskinan di Kapanewon Rongkop Kabupaten Gunungkidul - Afriyanti, Rosalia Widhiastuti Sri Lestari (Jurnal Masyarakat dan Desa, 2021)
Poverty is still be a attractive researcrh topic. Kapanewon Rongkop has been proclaimed as a center for the development of science and technology. It is interesting to see the use of Village Funds for poverty reduction. This research focuses on identifying poverty reduction programs. This research aims to identify: (1) the amount of Village Funds used for poverty reduction programs; and (2) programs that are realized for poverty reduction in Rongkop subdistrict, Gunungkidul Regency. The research methods are descriptive with quantitative and qualitative approaches. The research location is in Rongkop subdistrict, Gunungkidul Regency. Data was collected by using interview, observation, and documentation techniques. The analytical methods used are descriptive statistics and qualitative analysis consists of: collection, reduction, presentation, and conclusion/verification. The results shows that: (1) the amount of the Village Funds used for poverty reduction in 2019 is 24,14%, in 2020 is 45,69%, an in 2021 is 59,24% of total Rongkop subdistrict Village Funds. From 2019-2021 the amount of Village Funds realization for poverty reduction programs has increased; and (2) poverty reduction programs implemented in Rongkop subdistrict during 2019-2021 consists of: provision of health facilities for residents such as latrines; provision or develeopment or improvement of clean water; and rehabilitation or construction of uninhabitable houses. There aren’t many business strengthening and training programs held so need to improved